Progressão da periodontite experimental em ratas diabéticas submetidas ao tratamento com dose oncológica de zoledronato - Mello Neto, João Martins de [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Objetivo: O objetivo do presente estudo foi avaliar a progressão da periodontite experimental (PE) em ratas diabéticas submetidas à terapia com dose oncológica de zoledronato. Materiais e métodos: 120 animais (12 meses de idade) foram distribuídos aleatoriamente em quatro grupos experimentais: VEI-NG (n=30); VEI-DM (n=30), ZOL-NG (n=30) e ZOL-DM (n=30). Durante 7 semanas, a cada 3 dias, administrou-se pela via intraperitoneal 0,45ml de solução de NaCl 0,9% (VEI-NG e VEI-DM) ou 0,45ml desta solução acrescida de 100 µg/Kg de zoledronato (ZOL-NG e ZOL-DM). No 14º dia todos os animais foram submetidos: 1) indução da PE; 2) indução da diabetes com dose única de 0,3 ml de solução de estreptozotocina (60 mg/kg) diluída em solução de tampão citrato de sódio 0,1M, pH 4,0 (VEI-DM e ZOL-DM) ou apenas o veículo de tampão citrato (VEI-NG e ZOL-NG). As eutanásias foram realizadas aos 14, 21 e 35 dias após indução da PE. Foi realizada análise microtomográfica das hemimandibulas direitas e histopatológica e imunohistoquiímica (TNF-α e IL-1β) das hemimandibulas esquerdas. Os resultados foram analisados em microscopia óptica e submetidos à estatística com nível de significância de 5%. Resultados: A análise micro-CT mostrou uma menor perda óssea alveolar (POA), maior volume ósseo na furca (VOF) e maior espessura do trabeculado ósseo em ZOL-NG e ZOL-DM. ZOL-NG e ZOL-DM apresentaram maior porcentagem de tecido ósseo na furca (PTO) e a porcentagem de tecido ósseo não vital na furca (PON) foi maior em ZOL-DM. A resposta inflamatória periodontal foi maior em ZOL-NG e ainda maior em ZOL-DM, com inflamação mais intensa e nível das principais citocinas com atividade pró-inflamatória (TNFα e IL-1β) maior em ZOL e ainda maior em ZOL-DM. Conclusão: O diabetes mellitus promove exacerbação da resposta inflamatória periodontal ao longo do tratamento com dose oncológica de zoledronato, o que o coloca, juntamente com a doença periodontal, como um importante fator de risco para a osteonecrose dos maxilares.

The aim of the present study is to evaluate the progression of experimental periodontitis (PE) in diabetic female rats under therapy of oncological dosage of zoledronic acid. 120 female rats (12 months of age) were randomly assigned to four experimental groups: VEI-NG (n = 30); VEI-DM (n = 30), ZOL-NG (n = 30) and ZOL-DM (n = 30). For 7 weeks, every 3 days, 0.45 ml of 0.9% NaCl solution (VEI-NG and VEI-DM) or 0.45 ml of this solution plus 100 μg / kg zoledronate (ZOL) were administered intraperitoneally -NG and ZOL-DM). On the 14th day post-start of the experiment all animals were submitted to: 1) a ligature installation around the lower bilaterally first molar, which remained in position throughout the experimental period; 2) a caudal vein injection of 0.3 ml of streptozotocin solution (60mg/kg) diluted in 0.1 M sodium citrate buffer solution pH 4.0 (VEI-DM and ZOL-DM) or only the vehicle of sodium citrate buffer 0.1M, pH 4.0 (VEI-NG and ZOL-NG). As euthanasia were performed at 14, 21 and 35 days after the induction of PE by transcardiac perfusion with histological fixative. A microtomographic analysis of the right and posterior hemi-mandibles of the histological processing of the left hemi-jaw was performed. Patients with histories were submitted to hematoxylin-eosin staining or immunohistochemical reaction for: tumor necrosis factor alpha TNF-α and interleukin IL-1β. The results were analyzed by optical microscopy and submitted to statistical analysis with a significance level of 5%. The micro-CT analysis showed lower alveolar bone loss (POA), greater bone volume in the furcation (VOF) and greater thickness of bone trabecule in ZOL-NG and ZOL-DM compared to the VEI-NG and VEI-DM groups. ZOL-NG and ZOL-DM presented a higher percentage of bone tissue in the furcation (PTO) and a percentage of non-vital bone tissue in the furcation (PON) was higher in ZOL-NG and much higher in ZOL-DM. The periodontal inflammatory response was higher in ZOL-NG and even higher in ZOL-DM, with more intense inflammation and major cytokines with the higher pro-inflammatory activity (TNFα and IL-1β) in ZOL and even higher in ZOL-DM. Diabetes mellitus promotes exacerbation of the periodontal inflammatory response during treatment with the oncologic dose of zoledronate, which causes, along with periodontal disease, an important risk factor for osteonecrosis of the jaw.
Experimental periodontitis progression in diabetic rats submitted to treatment with zoledronate oncologic dose
Keywords: Difosfonatos; Osteonecrose; Periodontite crônica; Progressão da doença; Diabetes mellitus; Diphosphonates